ENGLISH LANGUAGE LEARNING IN NON-FORMAL SETTINGS: A CASE STUDY OF INDONESIAN CHILDREN IN A SANGGAR BELAJAR IN MALAYSIA - Arkana Hady; Fadly Ramadhan; Maslathif Dwi Purnomo (BRIGHT VISION, 2026)
This study explores how children learn English in a non-formal learning setting, specifically in a sanggar belajar attended by children of Indonesian migrant workers in Malaysia. The study aims to examine the learning processes, strategies and interactions that support learning, as well as the challenges faced by the students. A qualitative case study design was employed, with data collected through participant observation during a 40-minute teaching session and a semi-structured interview with the sanggar belajar teacher. The findings reveal that children learn English through imitation, interaction, active participation, and contextual use of language. Instructional strategies such as repetition, questioning, and simple dialogue practice were found to support students’ engagement and learning. However, the learning process is constrained by limited exposure to English, low confidence, varied proficiency levels, and restricted learning resources. These challenges are closely related to the students’ marginalized background as children of migrant workers, which affects their access to educational opportunities. The study concludes that English language learning in this context is not only a cognitive process but also a socially situated experience shaped by inequality and access. The findings suggest the need for adaptive teaching strategies, increased language exposure, and greater support for non-formal educational initiatives serving marginalized communities.Keywords: English Language Learning, Non-formal education, Marginalized children